2019
DOI: 10.1111/cote.12406
|View full text |Cite
|
Sign up to set email alerts
|

Natural colorant extraction from Cinnamomum camphora tree leaves of different maturities and its ultrasonic‐assisted extraction process

Abstract: This study investigated natural colorant extraction from camphor tree leaves using a green and effective process. Ethanol, acetic acid, aqueous sodium carbonate and an aqueous solution of cellulase enzyme were used to examine the extraction performance, with and without the assistance of ultrasonics. Results showed that when subjected to changes in frequency and extraction time, ultrasonics is able to accelerate the extraction process and achieve a better yield for chlorophyll and anthocyanin extraction from f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Additionally, the heat produced by the high-speed comminution process will have an impact on the thermally sensitive material. In recent years, there has been a lot of interest in using ultrasonic technology as a green extraction technique to separate natural compounds from plant materials [ [22] , [23] , [24] , [25] ]. With its energy-saving, high-efficiency, and robust operability, ultrasonic technology will cause the cavitation phenomenon, which will result in the formation of millions of tiny bubbles in the liquid, their growth, and eventual rupture.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the heat produced by the high-speed comminution process will have an impact on the thermally sensitive material. In recent years, there has been a lot of interest in using ultrasonic technology as a green extraction technique to separate natural compounds from plant materials [ [22] , [23] , [24] , [25] ]. With its energy-saving, high-efficiency, and robust operability, ultrasonic technology will cause the cavitation phenomenon, which will result in the formation of millions of tiny bubbles in the liquid, their growth, and eventual rupture.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of the ultrasonic‐assisted extraction method is accredited to the cavitation bubbles caused by the propagation of the ultrasound wave in the effective range (20‐50 kHz) through the extraction solvents 85 . The ultrasonic‐assisted method was recently used to extract flavonoid‐based, quinone‐based and curcuminoid‐based textile dyes from several botanical sources, with a higher colour yield than the conventional heat‐assisted method 86–88 . A few studies have reported alizarin extraction with ultrasonic assistance from Rubiaceae family plants.…”
Section: Extraction Methods Of Alizarin From Rubiaceae Family Plantsmentioning
confidence: 99%
“…85 The ultrasonic-assisted method was recently used to extract flavonoid-based, quinone-based and curcuminoid-based textile dyes from several botanical sources, with a higher colour yield than the conventional heat-assisted method. [86][87][88] A few studies have reported alizarin extraction with ultrasonic assistance from Rubiaceae family plants. For instance, Cuoco et al treated the roots of madder (Rubia tinctorum L.) in an aqueous methanol solution with 25 kHz ultrasound.…”
Section: Ultrasonic-assisted Extractionmentioning
confidence: 99%
“…Ultrasonic‐assisted extraction (UAE) [27–33] is an innovative technology that has gained prominence in color extraction and dyeing in different fields like food, textiles, etc. It involves using ultrasound waves into the mixture of solvent and item to be extracted at a low temperature to enhance extraction processes by breaking down cell structures and facilitating the release of color, but not allowing any hydrolysis of the colorant, as well as reducing the scope of color fading during fabric dyeing as required at a low temperature in the process [34–37] …”
Section: Introductionmentioning
confidence: 99%
“…Generally, animal and plant cell walls are a high source of natural colors, but they are highly sensitive to hot water because the processing of color extraction at high temperatures breaks down some of the groups that restrict the process and demands cost-effective, sustainable methods. [20][21][22][23][24][25][26] Ultrasonic-assisted extraction (UAE) [27][28][29][30][31][32][33] is an innovative technology that has gained prominence in color extraction and dyeing in different fields like food, textiles, etc. It involves using ultrasound waves into the mixture of solvent and item to be extracted at a low temperature to enhance extraction processes by breaking down cell structures and facilitating the release of color, but not allowing any hydrolysis of the colorant, as well as reducing the scope of color fading during fabric dyeing as required at a low temperature in the process.…”
Section: Introductionmentioning
confidence: 99%